Educação do campo no território abaetetubense: análise da formação de professores(as) com base no Plano Municipal de Educação - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The present research addresses the issue of teacher training for working in rural schools in the abaetetubense territory. It originated from the following question: How is the formation of rural teachers being developed in the Abaetetetubense territory based on the analysis of the Municipal Education Plan? The general objective was to analyze the development of the formation of rural teachers in the Abaetetetubense territory based on the Municipal Education Plan of Abaetetuba. As specific objectives: 1) to historicize the formation of the master's student and his relation with the study object; 2) to problematize the historical, theoretical and legal aspects of the Field Education and the formation of teachers to act in the field schools; 3) to study the formation of teachers to act in the field schools in the Abaetetetubense territory from its determinations and analysis categories (Field Education and territory; 4) to evaluate, through the goals and strategies of the Educational Plans, if the formation of teachers to act in the rural schools in the territory of Abaetetubense has been developed in contradiction or not, with the conception and the educational policies of Field Education. The theoretical field about teacher's formation of Campo Education is based on studies of authors such as Caldart (2002); Arroyo (2007); Alencar (2010); Molina and Antunes-Rocha (2014); Borges (2015), among others, who approach the theme from a critical perspective, in opposition to the hegemonic social order rooted in society, so that it is possible to build new ways of thinking and doing education and teacher's formation as an instrument of political and social transformation. The methodological path of the Corpus of the Research, is grounded in the Historical-Dialectical Materialism, involving Bibliographic Research and Documentary Research in which the following primary documents were analyzed: a) National Education Plan (PNE/2014-2024); b) Pará State Education Plan (PEEPA/2015-2025); c) Abaetetuba Municipal Education Plan (PME-Abaetetuba/2015-2025). In addition to the following secondary documents: Planning the Next Decade: knowing the 20 goals of the National Education Plan; Base Document of the State Education Plan/PA; Report of the Integrated System of Monitoring, Execution and Control (SIMEC) that dispose the Evaluation Diagnosis of the PME of Abaetetuba. The result of the analysis showed advances in relation to Field Education in the educational plans, such as a greater number of strategies and the incorporation of the term Field Education in the plans, especially in the PNE, becoming the first to consider the representativeness of the social movements of the field compared to the previous ones that used Rural Education. Regarding teacher training, it was identified in the PNE the predominance of a conception of neoliberal, technical training with authoritarian and conservative views, based on the epistemology of practice that reinforces the hegemonic ideological discourse, making the autonomy of teachers invisible, moving away from an omnilateral training based on epistemological praxis that seeks to develop the teaching work based on educational, ethical, and political principles, approaching the conception of Rural Education. Regarding the development of teacher training to work in rural schools in the territory of abaetetubense, it was concluded that this training has been developed in a weakened way, because many goals and strategies that mention rural education and teacher training to work in rural schools are not being achieved.
Field education in the abaetetetubense territory: analysis of teacher training based on the Municipal Education Plan
Keywords: Educação rural - Abaetetuba (PA); Escolas rurais - Abaetetuba (PA); Professores - Formação - Abaetetuba (PA); CIENCIAS HUMANAS; Educação do campo; Formação de professores (as); Planos educacionais; Abaetetuba